Key policy objectives for European agricultural policies: some reflections about the policy coherence - Silvia Coderoni (Bio-based and Applied Economics, 2023)
Food security and environmental sustainability are joint global challenges that require to be solved together. A complex policy framework is needed to tackle this conundrum as policy coherence (PC) is fundamental but extremely challenging. This analysis, after stressing the importance of solving jointly the challenges of producing enough food to feed a growing population while preserving the climate and the environment, discusses some issues related to the PC approach that should be followed. Within and between coherence problems are assessed and discussed and governance problems related to the PC approach are presented. Key points for a likely approach to PC include goal-based governance grounded on the analytical analysis of synergies and trade-offs.